2022
DOI: 10.1038/s41467-022-31358-5
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of m6A modification on mRNA partitioning into stress granules

Abstract: The presence of the m6A modification in mammalian mRNAs is proposed to promote mRNA recruitment to stress granules through the interaction with YTHDF proteins. We test this possibility by examining the accumulation of mRNAs in stress granules in both WT and ∆METTL3 mES cells, which are deficient in m6A modification. A critical observation is that all m6A modified mRNAs partition similarly into stress granules in both wild-type and m6A-deficient cells by single-molecule FISH. Moreover, multiple linear regressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 35 publications
(47 reference statements)
5
40
0
Order By: Relevance
“…The SG transcriptome is highly enriched for m6A-modified mRNAs relative to total cellular mRNA, with a strong correlation between the extent of m6A modification and partitioning to SGs. ,, However, >97% of transcripts contain four or fewer m6A sites, and these sites are modified at rates of less than 100% . More recent bioinformatic analyses suggest that mRNA length has a stronger impact on SG partitioning than the presence of m6A sites . In terms of mechanism, m6A modifications are catalyzed by a writer complex comprising METTL3, METTL14, and WTAP and are recognized by the YTH domain-containing proteins YTHDF1/2/3, which variably colocalize with SGs following stress treatments. ,,,, It should be noted that genetic depletion of writer complex components significantly reduces the accumulation of m6A-modified mRNAs in SGs, although SG formation is not impaired. , While these data are based on the detection of mRNAs in bulk, a more quantitative evaluation of 11 different mRNAs did not reveal any significant differences in SG partitioning between wild-type cells and a mettl3 knockout .…”
Section: Regulation Of Stress Granule Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SG transcriptome is highly enriched for m6A-modified mRNAs relative to total cellular mRNA, with a strong correlation between the extent of m6A modification and partitioning to SGs. ,, However, >97% of transcripts contain four or fewer m6A sites, and these sites are modified at rates of less than 100% . More recent bioinformatic analyses suggest that mRNA length has a stronger impact on SG partitioning than the presence of m6A sites . In terms of mechanism, m6A modifications are catalyzed by a writer complex comprising METTL3, METTL14, and WTAP and are recognized by the YTH domain-containing proteins YTHDF1/2/3, which variably colocalize with SGs following stress treatments. ,,,, It should be noted that genetic depletion of writer complex components significantly reduces the accumulation of m6A-modified mRNAs in SGs, although SG formation is not impaired. , While these data are based on the detection of mRNAs in bulk, a more quantitative evaluation of 11 different mRNAs did not reveal any significant differences in SG partitioning between wild-type cells and a mettl3 knockout .…”
Section: Regulation Of Stress Granule Dynamicsmentioning
confidence: 99%
“…In terms of mechanism, m6A modifications are catalyzed by a writer complex comprising METTL3, METTL14, and WTAP and are recognized by the YTH domain-containing proteins YTHDF1/2/3, which variably colocalize with SGs following stress treatments. ,,,, It should be noted that genetic depletion of writer complex components significantly reduces the accumulation of m6A-modified mRNAs in SGs, although SG formation is not impaired. , While these data are based on the detection of mRNAs in bulk, a more quantitative evaluation of 11 different mRNAs did not reveal any significant differences in SG partitioning between wild-type cells and a mettl3 knockout . Variable observations have also been obtained from analyses of YTHDF genetic knockdowns, ranging from a significant impairment of SG localization by m6A-modified mRNAs to no detectable effect, potentially due to differences in experimental approaches. , Overall, Khong et al posit that RNA targeting to SGs results from the cumulative contribution of multiple factors and that m6A modification plays a relatively minor role. Interestingly, SG RBPs such as G3BP1/2, RBM42, CAPRIN1, and USP10 preferentially bind unmethylated sequences over m6A-modified RNAs, , suggesting distinct mechanisms for methylation-dependent and -independent transcript recruitment into SGs.…”
Section: Regulation Of Stress Granule Dynamicsmentioning
confidence: 99%
“…[165,166] An argue study indicates that mRNA length, rather than m 6 A modifications, has a promotion effect on mRNA partitioning in SGs. [167] Additionally, m 6 A modifications were shown to repress RNA binding to G3BP1/2, ubiquitin-specific protease 10 (USP10), Caprin-1, and RNA-binding motif 4 (RBM4) which are linked to the formation of SGs. [168] Thus, the inconsistent observations above implicate that the role of m6A in SGs formation is still a debatable issue.…”
Section: Rna and Dna Modificationsmentioning
confidence: 99%
“…These findings collectively suggest that m 6 A modification might modulate SGs targeting of RNAs. However, a recent study has found that m 6 A modifications have limited effects on mRNA recruited into SGs ( 39 ). Thus, the relationship of m 6 A modification with SGs targeting remains to be elucidated.…”
Section: Components and Functions Of Sgsmentioning
confidence: 99%